Effects of air gap eccentricity on different rotor structures for PMSM in electric vehicles - Kartal, Emin Tarik; Arabul, Fatma Keskin (NATURE PORTFOLIO, 2024)
In addition to research related to static eccentricity and dynamic eccentricity examining fault and diagnostic methods in various types of motors, there are also studies conducted for motors with non-uniform air gaps similar to the condition. In these studies, improvements and changes in motor performance for such types of motors can be observed. In this study, the effects of the rotor structures determined in the study and the air gap shape, which is effective by changing the eccentricity ratio, on the motor performance of the interior permanent magnet synchronous motor designed for electric vehicle applications are examined. Besides the elliptical rotor structure, which is widely researched in dynamic eccentricity studies, these eccentric motor structures also include novel rectangular and polygonal eccentric rotor structures. Motor models with non-uniform air gap structures are designed in two dimensions and subjected to simulation and analysis studies using the finite element method. At the end of the study, along with the parameters identified for motor performance, the harmonic components of the stator current, radial air gap flux density and the output torque obtained through Fast Fourier Transform analysis have been provided.
Keywords: MAGNET SYNCHRONOUS MOTORS; FAULT-DIAGNOSIS; DEMAGNETIZATION FAULTS; MIXED-ECCENTRICITY; COGGING TORQUE; REDUCTION; VIBRATION; Science & Technology - Other Topics